Анализ критических режимов систем с динамической защитой от вредных воздействий - Прусаков, Н. А. (ХНУРЕ, 2012)
A model of the dynamic system describing the situation when the main subsystem "produces" a detrimental factor, and the second subsystem - defense - tries to reduce it completely, or at a reasonable price.
Keywords: модель динамической системы; автокуммулятивность; пакет Mathematica